The Influence of Product Quality, Price, and Promotion on Purchasing Decisions in Shopee E-Commerce in Batam City - Dira Citra Hendriani; Tiurniari Purba (Komunitas Dosen Indonesia, 2026)
Finding out how Batam City Shopee users evaluate products in relation to price, quality, and sales is the main goal of this research. The research employs quantitative methodologies that are grounded on a descriptive approach. Researchers used a Lemeshow-based purposive selection technique to choose 96 Shopee users from Batam City for the study. We utilized SPSS version 27's multiple linear regression to examine data collected from a Likert-scale questionnaire. The findings revealed that product quality had a statistically significant positive influence on consumer purchasing behaviour (t = 2.963, p = 0.004). Prices had a positive and statistically significant effect on consumers' decisions to buy (t-statistic = 3.479, p = 0.001). Advertising demonstrated the strongest effect on consumer buying behaviour, showing a statistically significant positive relationship (t = 4.782, p = 0.000). The combined Adjusted R Square indicated that quality of products, pricing, and promotional activities collectively accounted for a substantial 77.4% of the variation in consumer purchase choices. At the 0.000 level of significance, the F-statistic was 109.688.